LIFE SKILL EDUCATION (LSE) IN NON-FORMAL EDUCATION SETTING - Masyhud Masyhud (EDUCAFL : Journal of Education of English as Foreign Language, 2019)
Life Skill Education (LSE) equips individual to survive in the future. In addition, the importance of life skill cannot be neglected to assist young people to deal with challenges in life by having a skill that enable, equip and empower them with necessary behaviors. LSE is not only applicable in formal, but also informal education. In regards to that, this study tries to investigate the implementation of life skill in non-formal education setting. This qualitative study was conducted in two private libraries in Malang, TBM Wacan and TBM Merdesa with 10 members for each. Participatory observation and document analysis were equipped to gather the data. The result shows that three  aspects  in  life  skill,  which are  thinking  skill,  emotional  skill  and also social skill were explored. These aspects were then is formed in various activities such as poster creation, language games, disaster mitigation simulation, and role play.